Application of Trend Projection in Prediction of Animal Feed Sales at PT. Android-Based Charoen Pokphand Medan - Padang, Jefri (SEAN Institute, 2023)
PT. Charoen Pokphand Medan is a company engaged in the production and sale of animal feed on a large scale.In business processPT. Charoen Pokphand Medanevery day keeping records using paper as proof of sales and purchase transactions, if it continues like this it will cause problems if there is a missed sales and purchase history recap. PartyPT. Charoen Pokphand Medanconfusion is created because there is no calculation in buying goods so that the accumulation of the same goods often occurs in the warehouse. Stock data collection onPT. Charoen Pokphand Medanwhich has various types of goods and the recording of transactions needs to be computerized. So it is necessary to create a system to record every sale and purchase transaction so that every existing transaction can be stored in a computer database. This information system application can also perform forecasting which is useful for predicting how many items are sold in certain periods. This process is carried out to produce a prediction of the amount of animal feed that might be sold in the following month. So the system will help the company in checking animal feed stocks because it can estimate the need for goods so they don't run out of stock and determine the amount of stock in the future.